Inherited Thyroid Tumors With Oncocytic Change - Correia, Marcelo; Lima, Ana Rita; Batista, Rui; Máximo, Valdemar; Sobrinho-Simões, Manuel (Frontiers in Endocrinology, 2021)
Familial non-medullary thyroid carcinoma (FNMTC) corresponds to 5-10% of all follicular cell-derived carcinoma (FCDTC). Oncocytic thyroid tumors have an increased incidence in the familial context in comparison with sporadic FCDTC, encompassing benign and malignant tumors in the same family presenting with some extent of cell oxyphilia. This has triggered the interest of our and other groups to clarify the oncocytic change, looking for genetic markers that could explain the emergence of this phenotype in thyroid benign and malignant lesions, focusing on familial aggregation. Despite some advances regarding the identification of the gene associated with retinoic and interferon-induced mortality 19 (GRIM-19), as one of the key candidate genes affected in the “Tumor with Cell Oxyphilia” (TCO) locus, most of the mutations follow a pattern of “private mutations”, almost exclusive to one family. Moreover, no causative genetic alterations were identified so far in most families. The incomplete penetrance of the disease, the diverse benign and malignant phenotypes in the affected familial members and the variable syndromic associations create an additional layer of complexity for studying the genetic alterations in oncocytic tumors. In the present review, we summarized the available evidence supporting genomic-based mechanisms for the oncocytic change, particularly in the context of FNMTC. We have also addressed the challenges and gaps in the aforementioned mechanisms, as well as molecular clues that can explain, at least partially, the phenotype of oncocytic tumors and the respective clinico-pathological behavior. Finally, we pointed to areas of further investigation in the field of oncocytic (F)NMTC with translational potential in terms of therapy.